From pixels to pedagogy: using video games for higher education in the humanities - Jessica van Horssen; Zoe Moreton; Gaspard Pelurson (Journal of Learning Development in Higher Education, 2023)
This paper explores how video games can enhance learning in the higher education Humanities classroom through play and critical discussions. Through the observation of two case studies, it aims to highlight important concepts and considerations and serve as a platform for future research and debate. The first case study utilised Sid Meier’s Civilization IV: Colonization (Firaxis Games, 2008) and involved first-year History students. They were encouraged to take part in critical assessment and discussion by pairing gameplay with lecture content featuring the same moments in history they experienced in the game. This led to the students being able to better challenge historical narratives through holistic reflexive engagement. The second case study used GreedFall (Spiders, 2019) to encourage students to question historical inaccuracies and utopian diversity. Through connecting gameplay to module outcomes, students unconsciously adopted a critical eye which indicates how the game can be used to debate race, Western imagination, and imperialism. We conclude that gaming in the classroom is an engaging way to deliver content and it enables students to develop critical and reflexive thinking within playful spaces. As such, this article focuses on the students studying the humanities and discusses the video game as a medium to identify and analyse ideologies, and gaming as a way of developing reflexive critical thinking and analytic skills.